The Effect of Chinese Medicine on Lipid and Glucose Metabolism in Acute Myocardial Infarction Through PPARγ Pathway - Zhang, Qian; Shao, Mingyan; Zhang, Xuefeng; Wang, Qiyan; Guo, Dongqing; Yang, Xiaomin; Li, Chun; Wang, Yong (Frontiers in Pharmacology, 2018)
Aim: Danqi pill (DQP), a Chinese medicine frequently prescribed in China, has been approved to improve cardiac function by regulating cardiac energy metabolism in heart failure (HF) after acute myocardial infarction (AMI) patients. The aim of this study was to explore whether the mechanism of DQP is associated to the lipid and glucose metabolism mediated via PPARγ (peroxisome proliferator-activated receptor γ) pathway both in vivo and in vitro. Methods and Materials: Model of HF after AMI was established with ligation of left anterior descending artery on Sprague-Dawley (SD) rats. 28 days after treatment, hematoxylin-eosin (HE) staining was applied to visualize cardiomyocyte morphological changes. High performance liquid chromatography (HPLC) was performed to assess the contents of adenosine phosphates in heart. Positron emission tomography and computed tomography (PET-CT) was conducted to evaluate the cardiac glucose metabolism. Expressions of key molecules such as PPARγ, sterol carrier protein 2 (SCP2) and long chain acyl CoA dehydrogenase (ACADL) were measured by western blotting (WB) and immunohistochemistry (IHC). Oxygen-glucose deprivation-reperfusion (OGD/R)-induced H9C2 injury cardiomyocyte model was adopted for potential mechanism research in vitro. Results: Treatment with DQP rescued hearts from structural and functional damages as well as inflammatory infiltration. Levels of adenosine triphosphate (ATP) and energy charge (EC) in DQP group were also up-regulated compared to model group. Further results demonstrated that critical enzymes both in lipid metabolism and glucose metabolism compromised in model group compared to sham group. Intriguingly, DQP could up-regulate critical enzymes including ACADL and SCP2 in lipid metabolism accompanying with promoting effect on molecules in glycolysis simultaneously. Results on upstreaming signaling pathway demonstrated that DQP could dramatically increase the expressions of PPARγ. In vitro study suggested the efficacy of DQP could be blocked by T0070907, a selective PPARγ inhibitor. Conclusion: DQP has cardioprotective effect in improving cardiac function and energy metabolism through regulating lipid and glucose metabolism. The effects may be mediated by PPARγ pathway.